(untitled) - McLachlan, Geoffrey J. (Hoboken, N.J, 2004)
Analyzing Microarray Gene Expression Data provides a comprehensive review of available methodologies for the analysis of data derived from the latest DNA microarray technologies. Designed for biostatisticians entering the field of microarray analysis as well as biologists seeking to more effectively analyze their own experimental data, the text features a unique interdisciplinary approach and a combined academic and practical perspective that offers readers the most complete and applied coverage of the subject matter to date.
Keywords: Gene expression,DNA microarrays,DNA vi mạng,Biểu hiện gen; Statistical methods,Statistical methods,Các phương pháp thống kê,Phương pháp thống kê